Analysis of cancellations of surgery for benign prostatic hyperplasia after patients are taken to the operating room: A retrospective single-center study (Annals of Medical Research, 2025)
Aim: This study aims to evaluate the reasons for canceling elective surgeries for benign prostatic hyperplasia (BPH) after patients are taken to the operating room.Materials and Methods: Data from 1743 cases scheduled for elective surgery due to BPH that were taken to the operating room between December 2011 and June 2024 were retrospectively analyzed. The demographic data, American Society of Anesthesiologists (ASA) status, reasons for cancellation. The clinical course of the 89 patients (5.1%) whose surgeries were canceled in the operating room were evaluated.Results The mean age of the patients whose surgeries were canceled in the operating room was 69.2 ± 11.68 years. The most common reasons for surgical cancellations were cardiovascular system-related pathologies, such as uncontrolled hypertension (33.7%) and abnormal electrocardiographic changes (12.4%).  Eighty-five (95.5%) patients had an ASA status of 3 or higher. The surgeries of 80 (89.9%) patients were successfully performed at a later date in our hospital. It was determined that 87.64% of the cancellations could have been avoidable.Conclusion: Our study found that 5.1% of elective surgeries due to BPH were cancelled, and most were avoidable. We believe that rigorous and optimized preoperative patient assessment is crucial in preventing surgical cancellations, especially in procedures involving an elderly population, such as surgeries for BPH.
Keywords: Benign prostatic hyperplasia; Elective surgery; Cancellation; Perioperative care; Pre-operative management; Operating room